AFLATOXIN B1 CONTAMINATION IN THE RATION OF LACTATING DAIRY COW AND REDUCTION OF ITS CARRY-OVER INTO THE MILK - , IKA SUMANTRI ([Yogyakarta] : Universitas Gadjah Mada, 2014)
This dissertation research is consisted of 4 studies, those are: (1) survey to obtain data on the occurrence and levels of aflatoxin B1 (AFB1) contamination in dairy feed and aflatoxin M1 (AFM1) in raw milk from dairy farming, dairy cooperatives, and feedmills